PENGARUH RETURN ON INVESTMENT DAN PRICE EARNING RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR FARMASI DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Saprudin Saprudin; Arno Sebastian; Maya Mustika (Journal of Information System, Applied, Management, Accounting and Research, 2020)
The purpose of this study was to determine the effect of Return on Investment and Price Earning Ratio on stock prices, either partially or simultaneously on manufacturing companies in the Pharmaceutical Industry sector on the Indonesia Stock Exchange during 2014-2018. Data was obtained from direct observation and documentation from the IDX Yearly Statistics and daily trading reports published by The Indonesia Capital Market Institute. Data analysis in this research uses descriptive analysis method and quantitative statistical analysis using SPSS 22 for windows program. Partially the results of the study show that Return on Investment has a significant influence on stock prices and Price Earning Ratio also has a significant effect on stock prices. Simultaneously Return on Investment and Price Earning Ratio have a significant influence on stock prices. So management needs to increase the growth in the value of ROI, and keep the PER value high.